Canonical transient receptor potential 6 channel deficiency promotes smooth muscle cells dedifferentiation and increased proliferation after arterial injury - Smith, Andrew H. (2020)
Fil: Smith, Andrew H. Clínica Cleveland. Departamento de Cirugía Vascular; Estados Unidos